Prevalence and genotyping distribution of Enterocytozoon bieneusi in diarrheic pigs in Chongqing and Sichuan provinces, China - Ghebremichael, Samson Teweldeberhan; Meng, Xianzhi; Wei, Junhong; Yang, Yujiao; Huang, Qingyuan; Luo, Lie; Xiang, Heng; Chen, Jie; Abo-Kadoum, M. A.; Li, Tian; Liu, Xiao; Bao, Jialing; et al. (Frontiers in Microbiology, 2022)
The microsporidian fungal pathogen, Enterocytozoon bieneusi, is a unicellular organism that infects various animal hosts, including pigs and humans. E. bieneusi infection is scant in diarrheic pigs in Chongqing and Sichuan provinces, China. This study aims to determine the prevalence and genotype distribution of E. bieneusi in diarrheic pigs. In total, 514 fecal samples from diarrheic pigs were obtained from 14 large-scale farms in Chongqing and Sichuan provinces (320 suckling, 23 weaned pigs, 65 fattening pigs, and 106 sows). To identify the genotype(s) of E. bieneusi, genomic DNA was isolated from the samples and tested by nested-PCR (nPCR), targeting the internal transcribed spacer (ITS) region of rRNA and followed by DNA sequence analysis. The prevalence of E. bieneusi was found to be 79.8% (410/514), with rates of 84.9% (90/106) in sows and 69.5 % (16/23) in weaned pigs. We found 61 different ITS genotypes, including seven known genotypes (E, F, CHG1, Peru8, CAF1, B and BEB17) and 54 novel genotypes (PigCE01(7), PigCE02(6), PigCE03(2), PigCE04(1), PigCE05(1), PigCE06(5), PigCE07(12), and PigCE08(20)). Phylogenetically, all of the discovered genotypes clustered with counterparts belonging to group 1 and group 2 of E. bieneusi. To the best of our knowledge, this research article is the first report of E. bieneusi and a higher prevalence in sows than pre-weaned and weaned pigs in a diarrheic pig in China. These findings highlight those diarrheic pigs could be a potential reservoir host, which can contaminate the environment and be a source of microsporidiosis in humans and other animals.